Effect of a second treatment with prostaglandin F2α during the Ovsynch protocol on luteolysis and pregnancy in dairy cows (2015)
The main objective of this study was to evaluate the effect of a second treatment with prostaglandin F2α (PGF) during Ovsynch on regression of the corpus luteum (CL) and on fertility to the timed artificial insemination. Two experiments were performed. In both experiments, cows were randomized to receive (1) no additional treatments with PGF = 1 PGF, or (2) a second PGF treatment at 24 h after the first PGF treatment = 2 PGF. The first experiment (n = 344 synchronized lactating dairy cows that received artificial insemination at 81 ± 3 d in milk) used the Double-Ovsynch protocol for synchronizing ovulation. Blood samples were collected at the PGF and final GnRH treatments (72 and 16 h before timed artificial insemination) during the breeding Ovsynch protocol, to determine CL regression in response to the protocol. Treatment with 2 PGF increased CL regression from 83.0% with 1 PGF to 97.0% with 2 PGF. The effect of 2 PGF on CL regression was observed in both primiparous and multiparous cows. Cows with lower (2.0 to 4.8 ng/mL) versus greater (4.9 to 12.0 ng/mL) circulating progesterone at the time of PGF had lower percentage of cows with complete CL regression after 1 PGF (66.7 vs. 88.1%) but not after 2 PGF (95.1 vs. 97.6%). Experiment 2 used 2,148 lactating dairy cows on 11 dairy farms in 4 different regions of the United States. Cows were synchronized with Ovsynch and received timed artificial insemination at 60 ± 3 d in milk. Cows that received 2 PGF had a tendency for increased pregnancies per artificial insemination (P/AI) compared with cows with 1 PGF (36.1 vs. 33.3%). This tendency for improvement in P/AI was observed in multiparous but not in primiparous cows. Combining data from the 2 experiments indicated a 9.45% relative increase in P/AI for cows receiving 2 compared with 1 PGF (37.6 vs. 34.4%) with the increase in P/AI observed in multiparous but not in primiparous cows. Thus, a second PGF treatment in Ovsynch-type protocols can increase pregnancy success by about 10%, primarily due to enhanced fertility in multiparous cows.